Infographic. Video analysis of match hamstring injury patterns in professional male football (soccer) teaches us about the need for demand-specific multicomponent exercise-based risk reduction programmes - Gronwald, T.; Klein, C.; Hoenig, T.; Pietzonka, M.; Bloch, H.; Edouard, P.; Hollander, K. (British Journal of Sports Medicine, 2022)
Although hamstring injuries represent a high proportion of injuries and a high injury burden in professional football, little attention has been given to understanding typical patterns of hamstring injuries. Understanding injury causation represents one key factor in injury risk mitigation. We conducted a systematic video analysis to investigate inciting events of hamstring injuries in professional male football players. We analysed 52 moderate and severe (ie, time loss of >7 days) acute non-contact (n=34) and indirect contact (n=18) match hamstring injuries across four seasons (2014-2019) of the two highest divisions in German male football (Bundesliga; 2. Bundesliga). The pattern analysis revealed 25 sprint-related injury patterns (48%, non-contact: 22, indirect contact: 3) and 27 stretch-related injury patterns (52%, non-contact: 12, indirect contact: 15) (figure 1).